2004
DOI: 10.1021/es049895w
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Bacterial Organomercury Lyase (MerB) in Controlling Methylmercury Accumulation in Mercury-Contaminated Natural Waters

Abstract: The curious phenomenon of similar levels of methylmercury (MeHg) accumulation in fish from contaminated and pristine environments may be explained by the observation that the proportion of total mercury (HgT) present as MeHg is inversely related to HgT in natural waters. We hypothesize that this "MeHg accumulation paradox" is explained by the quantitative induction of bacterial enzymes that are encoded by the mercury resistance (mer) operon, organomercury lyase (MerB), and mercuric reductase (MerA) by inorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
163
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(171 citation statements)
references
References 61 publications
6
163
2
Order By: Relevance
“…However, further research is needed to determine more adequately the co-selection for antibiotic-resistant strains, particularly of pathogenic species to humans and animals. It has been proposed that bacterial-mediated attenuation mechanisms may result in a decrease of Hg levels in aquatic systems [3,18]. The results of the present study clearly show the existence of indigenous bacterial strains with such a potential in El Callao tailing ponds.…”
Section: Discussionsupporting
confidence: 63%
“…However, further research is needed to determine more adequately the co-selection for antibiotic-resistant strains, particularly of pathogenic species to humans and animals. It has been proposed that bacterial-mediated attenuation mechanisms may result in a decrease of Hg levels in aquatic systems [3,18]. The results of the present study clearly show the existence of indigenous bacterial strains with such a potential in El Callao tailing ponds.…”
Section: Discussionsupporting
confidence: 63%
“…In low contamination sites the three macroalgae present similar responses, suggesting that no specific decontamination strategy is occurring. Organic mercury results show a similar pattern (increased percentage of organic mercury in low contamination situation) to that of planktonic communities from contaminated and pristine environments (Schaefer et al, 2004). Adaptation to contamination and enhanced reductive demethylation rates may explain this feature (Schaefer et al, 2004).…”
Section: Discussionmentioning
confidence: 71%
“…Unlike lotic and organic-rich systems, where sediment MeHg may remain bound in the sediment matrix due to sulfide complexation (Marvin-DiPasquale et al, 2000;Kamman et al, 2004), sediments of rivers, with their higher relative %MeHg values, may provide an important source of MeHg to the food web. Schaefer et al (2004) describe a similar inverse relationship between aqueous HgT and %MeHg in several waterbody types. Using experimental evidence, they showed that reduced %Hg as MeHg in higher HgT systems is the result of active demethylation and subsequent Hg reduction by bacteria that posses organomercury lyase enzymes known as ''MerB'' and MerA.''…”
Section: Factors Influencing Mercury In Freshwater Surface Sediments 105mentioning
confidence: 63%